Successful focal ablation in a patient with electrical storm in the early postinfarction period: case report - Aksu, Tolga (Int Med Case Rep J, 2015)
Electrical storm (ES) is associated with a poor prognosis if it occurs in the early postinfarction period (within 4 weeks). There are limited data on the efficacy and safety of catheter ablation in the early period. In the patients with postinfarction cardiomyopathy, ventricular tachycardia (VT) is usually caused by re-entry through slowly conducting tissue within areas of a myocardial scar, whereas for the early postinfarction period, the underlying mechanism of ES is not fully understood. We report a case of ES for which macroreentry was excluded as a mechanism of VT because of the clinical and electrophysiological properties of the tachycardia. The tachycardia was terminated by focal radiofrequency catheter ablation of the earliest site. The total procedure time was only 35 minutes. During a 12-month follow-up period, the patient has remained free of monomorphic VT episodes. On the basis of this case, we aimed to discuss the underlying mechanism of ES in the early postinfarction period and to evaluate the role of radiofrequency catheter ablation as a primary approach for treating ES.